2020
DOI: 10.3389/fpsyt.2020.00718
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cathepsins in Memory Functions and the Pathophysiology of Psychiatric Disorders

Abstract: Cathepsins are proteases with functions in cellular homeostasis, lysosomal degradation and autophagy. Their role in the development of neurodegenerative diseases has been extensively studied. It is well established that impairment of proper cathepsin function plays a crucial role in the pathophysiology of neurodegenerative diseases, and in recent years a role for cathepsins in mental disorders has emerged given the involvement of cathepsins in memory function, hyperactivity, and in depression-and anxiety-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 70 publications
(109 reference statements)
1
11
0
Order By: Relevance
“…Several cathepsins have been shown to interact with and modulate tau spreading. As previously mentioned, these proteases are mainly localized to lysosomes, but they can also be secreted in the extracellular space (Boonen et al, 2016;Vidak et al, 2019;Niemeyer et al, 2020). Whilst the majority of data on the action of cathepsins on tau mostly reflects their activity in lysosomes, independent experiments have been conducted either in vitro using recombinant proteins or using cathepsin knockout animals.…”
Section: Proteasesmentioning
confidence: 99%
“…Several cathepsins have been shown to interact with and modulate tau spreading. As previously mentioned, these proteases are mainly localized to lysosomes, but they can also be secreted in the extracellular space (Boonen et al, 2016;Vidak et al, 2019;Niemeyer et al, 2020). Whilst the majority of data on the action of cathepsins on tau mostly reflects their activity in lysosomes, independent experiments have been conducted either in vitro using recombinant proteins or using cathepsin knockout animals.…”
Section: Proteasesmentioning
confidence: 99%
“…It also can affect various intracellular signaling pathways with the processing of several cytokines and chemokines 17 . CTSB plays a key role in many physiological and pathological processes such as cell proliferation, migration, autophagy, antigen presentation, apoptosis 19 , hippocampal dependent memory function 20 , cell differentiation and tumorigenesis 17 .…”
Section: Introductionmentioning
confidence: 99%
“…AD is distinguished by hippocampal-dependent dysfunction, cathepsins are also important for hippocampal-dependent learning and memory. It is reported that, cathepsins on being secreted in the extracellular space produces extracellular effects on synaptic plasticity and neuroprotection thereby playing role in AD (Niemeyer et al 2020). The results of Enrichment analysis were also found compatible with the correlation between targets and phenotypes in VarElect Analysis.…”
Section: Discussionmentioning
confidence: 99%